Analisis Pengaruh Pertumbuhan Ekonomi, Inflasi, Dan Nilai Tukar Mata Uang Asing Terhadap Profitabilitas Bank Umum Syariah Di Indonesia Periode 2016-2020 - Muzakki, Luthfi Akmal (Jurnal Ilmiah Ekonomi Islam, 2024)
This study aims to determine the effect of macroeconomic variables, namely economic growth, inflation and foreign exchange rates on the profitability of Islamic banks in Indonesia. The data sources for macroeconomic variables in this study are secondary data published by BPS and SEKI, while the profitability data for 14 Islamic banks in Indonesia are taken from the OJK Sharia Banking Statistics. The research method used in this study is a quantitative method with panel data analysis. The results showed that there was no significant effect of macroeconomic variables, namely economic growth, inflation and exchange rate variables on the profitability of Islamic banks partially, but simultaneously significant.